Controlling Dendrite Growth in Solid-State Electrolytes - Liu, He; Cheng, Xin-Bing; Huang, Jia-Qi; Yuan, Hong; Lu, Yang; Yan, Chong; Zhu, Gao-Long; Xu, Rui; Zhao, Chen-Zi; Hou, Li-Peng; He, Chuanxin; Kaskel, Stefan; et al. (ACS Energy Letters, 2020)
Solid-state electrolytes (SSEs) are widely considered as an "enabler" to inhibit dendrite growth of lithium-metal anodes for high-energy and highly safe next-generation batteries. However, recent studies demonstrated that lithium dendrites form in working SSEs. Theoretically, dendrite inhibition can be achieved in perfect SSEs without any defects, while dendrite growth is extensively observed in practical SSEs with poor interface stability, large grain boundaries, voids, and partial electronic conductivity. In this Review, dendrite growth behaviors in SSEs, including polymer and inorganic electrolytes, are comprehensively summarized. The observed dendrite morphology in these SSEs, possible formation mechanisms, and some solutions are analyzed. Clear perspectives and some suggestions are also presented for the further development of SSEs in lithium-metal batteries. This Review intends to shed fresh light on the understanding of dendrite growth in SSEs and the rational design of the architecture and materials for SSEs matching the lithium-metal anode.
CRIS-Team Scopus Importer:2022-04-14